The The Effect of Electrodeposition Voltage on the Antioxidant Activity of Gold Nanoparticles - Suliasih, Babay Asih; Sakinah, Anis; Marissa Angelina (Chemistry and Materials, 2024)
Gold nanoparticles (AuNPs) are well known as free radical scavengers, which may induce cell damage, triggering degenerative diseases and premature aging. This research aims to assess the antioxidant activity of AuNPs synthesized via the electrodeposition method, employing cyclic voltammetry on a Fluorine-doped Tin Oxide (FTO) substrate. By varying the initial voltage, the resulting AuNPs exhibit  variations in both particle size and number. In this study, AuNPs demonstrated promising antioxidant potential, particularly at an initial voltage of -1 V, as evidenced by their ability to respond to DPPH radicals, yielding a percent inhibition of up to 36.80%.